Hubungan Kecerdasan Kinestetik dengan Motivasi Belajar Peserta Didik Fase E pada Pembelajaran Biologi di SMAN 4 Sumatera Barat - Irmayeni, Novirsa; Fuadiyah, Sa’diatul (Lembaga Yasin AlSys, 2024)
This research is based on the problem of the lack of motivation to learn phase E students in learning Biology at SMAN 4 West Sumatra. In addition, the kinesthetic intelligence of students at SMAN 4 West Sumatra is more dominant. This study aims to determine the relationship between kinesthetic intelligence and learning motivation of phase E students in learning Biology at SMAN 4 West Sumatra. how much contribution is given and the results are related or not related. This research is descriptive correlation research. The research instrument used is a questionnaire in tabular form. The population amounted to 107 people and the sample amounted to 73 students. The results showed that there was a positive and significant relationship between kinesthetic intelligence and learning motivation with the strength of the relationship between kinesthetic intelligence and learning motivation of phase E students in Biology learning at SMAN 4 West Sumatra classified as very weak.